Dual-drug nanocomposite particles, hydrogel composites comprising the same, and tissue engineered meniscus, and methods of making and using the same

CN122955022APending Publication Date: 2026-10-23WEIFANG MEDICAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202611435597.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-23

AI Technical Summary

Benefits of technology

1.根据本申请的双药纳米复合颗粒及包含其的水凝胶复合物和组织工程半月板以及制备方法和应用,根据骨关节炎相关半月板损伤过程中早期炎症及氧化应激与后续病理性血管生成相互关联的病理特点,将木犀草素和舒尼替尼设置为具有不同空间位置和释放方式的双药组分,使木犀草素优先释放以改善早期炎症及氧化应激环境,并使舒尼替尼在此后持续释放以调控病理性血管生成。由此使药物释放顺序与半月板损伤后的病理过程相匹配,而非在植入后对不同作用目的的药物进行无差别同步释放,有利于在炎症得到控制后进一步维持半月板再生所需的乏血管微环境,为BMSC向软骨细胞分化提供适宜条件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955022A_ABST
    Figure CN122955022A_ABST
Patent Text Reader

Abstract

The application relates to a dual-drug nano composite particle, a hydrogel composite containing the dual-drug nano composite particle, a tissue engineering meniscus, and a preparation method and application, and belongs to the technical field of biomedical materials, tissue engineering and drug delivery. The dual-drug nano delivery system comprises mesoporous silica nanoparticles, sunitinib and luteolin, wherein the sunitinib is loaded in the mesoporous channels of the mesoporous silica nanoparticles, the luteolin is connected with the amino group on the surface of the mesoporous silica nanoparticles to form a Schiff base, and a dual-drug nanoparticle is formed; the dual-drug nano delivery system is further dispersed in HC hydrogel formed by photo-crosslinking of o-nitrobenzyl alcohol modified hyaluronic acid and chondroitin sulfate methacrylate, and is mixed with bone marrow mesenchymal stem cells to be cast in a three-dimensional printing polycaprolactone meniscus support to construct a tissue engineering meniscus; through the combination of the dual-drug nanoparticle, the hydrogel and the three-dimensional support, an integrated material system can be provided for the reconstruction of the structure and function of the meniscus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a dual-drug nanocomposite particle, a hydrogel complex containing the same, a tissue-engineered meniscus, a preparation method, and applications, belonging to the fields of biomedical materials, tissue engineering, and drug delivery technology. Background Technology

[0002] Meniscus-related OA accounts for over 40% of osteoarthritis (OA) worldwide, making it the leading type of degenerative meniscus injury and a significant cause of knee pain and limited mobility in middle-aged and elderly individuals. The meniscus, a crescent-shaped fibrocartilage tissue, plays a vital role in shock absorption and providing overall mechanical stability to the knee joint. However, the medial region of the meniscus is avascular, relying solely on synovial fluid for limited nutrition. After injury, it cannot recruit sufficient repair cells and lacks the nutritional support for cell proliferation and differentiation, resulting in extremely weak natural regeneration capacity. Clinically, there is an urgent need for regenerative therapies, but current treatments have significant limitations. When conservative treatment for meniscus injuries fails to improve symptoms, or when the injury is severe, surgical intervention is necessary. This includes meniscus repair, suitable for young patients with tears close to the meniscus edge and good blood supply, which preserves the meniscus structure to the greatest extent possible, but the healing rate is extremely low; and partial meniscectomy, which removes the damaged area while preserving the healthy portion, reducing the impact on joint stability. However, about 40% of patients develop early signs of knee osteoarthritis, such as joint space narrowing, 5 years after partial meniscectomy, and the incidence of OA rises to 60% 10 years after surgery.

[0003] In recent years, the field of tissue engineering regeneration has continuously proposed new solutions to address the meniscus regeneration problem. Currently, domestic and international research on constructing biomimetic tissue-engineered menisci mainly focuses on the mechanical support required by the meniscus. Furthermore, existing technologies for meniscus regeneration and repair, such as Chinese patent applications CN122005941A and CN117915933A, emphasize the biomimetic reconstruction of meniscus structure and function, while neglecting the regulation of the pathological microenvironment accompanying meniscus injury. Chinese patent application CN121754724A only regulates early inflammation while ignoring the naturally hypovascular microenvironment in the meniscus region. Inflammatory responses activate the expression of angiogenesis factors, and pathological angiogenesis hinders in situ regeneration.

[0004] Unlike other tissue injuries, the pathological microenvironment following meniscal injury is not merely a single inflammatory response. Early meniscal injury and replacement are often accompanied by significant inflammation and oxidative stress. Inflammation-related signals further promote the expression of angiogenesis-related factors, altering the previously hypovascular local microenvironment of the meniscus. Therefore, for tissue regeneration after meniscal injury, early inflammation control and subsequent control of pathological angiogenesis are not independent issues but rather linked by a continuous pathological process. If only early inflammation is targeted, pathological angiogenesis may still adversely affect the regenerating microenvironment of the meniscus even after inflammation subsides. Conversely, if drugs with different objectives are released simultaneously without distinguishing these pathological processes, it is difficult to match the drug action sequence with the pathological progression following meniscal injury.

[0005] Achieving meniscus regeneration first requires reversing the interference of the immune microenvironment, including anti-inflammatory and antioxidant agents, on regeneration conditions. For example, existing research has shown that loading drugs such as ibuprofen and diclofenac sodium into scaffolds can effectively inhibit macrophage polarization; however, due to drug toxicity, poor biocompatibility, and other side effects, the long-term efficacy remains unclear. Furthermore, carrying anti-inflammatory and chondrogenic factors (such as TGF-β) limits the control of drug loading and release in delivery systems, and makes material preservation and transportation conditions more stringent.

[0006] Current technologies cannot simultaneously improve the diverse pathological microenvironment of meniscus injuries while also restoring meniscus structure and function. Furthermore, while various mesoporous silica carrier delivery schemes exist in drug delivery systems (e.g., Chinese patent applications CN122297779A and CN122251238A), these technologies merely load a single material within mesoporous channels or graft it onto a surface. The carrier itself only acts as a "pocket," failing to functionalize the mesoporous silica carrier itself and regulate its drug release behavior in accordance with the characteristics of the local pathological microenvironment of meniscus injuries. Moreover, single drug loading modes cannot synergistically exert anti-inflammatory, antioxidant, and chondrogenic effects within the same delivery system, making it difficult to simultaneously achieve pathological microenvironment reversal and integrated meniscus structural and functional reconstruction. Therefore, the overall effectiveness of existing mesoporous silica delivery systems in meniscus regeneration and repair remains significantly limited.

[0007] Therefore, for meniscus repair, the key issue is not simply increasing the loading of a particular drug or prolonging its release time, but rather enabling the delivery system to recognize and respond to the pathological microenvironment at the injury site. This means ensuring that drugs with different objectives exert their effects sequentially according to the changes in the pathological microenvironment after meniscus injury. Specifically, this means prioritizing the improvement of the inflammatory microenvironment during the early stages of inflammation and oxidative stress, and then continuously inhibiting pathological angiogenesis after inflammation is controlled, thereby maintaining the hypovascular microenvironment necessary for meniscus regeneration. Simultaneously, the delivery system must adapt to the joint cavity environment after meniscus replacement, preventing rapid loss of drug carriers due to synovial fluid flushing, while also providing the necessary mechanical support for the meniscus defect.

[0008] Given the problems with existing technologies, designing a treatment system that can achieve stable drug loading, effectively correct inflammation, improve the microenvironment of pathological osteoarthritis, and promote meniscus cartilage regeneration remains an urgent problem to be solved.

[0009] It should be noted that the above background technology is only used to illustrate the research and development ideas of this application and does not necessarily constitute prior art. Summary of the Invention

[0010] In existing meniscus tissue engineering programs, issues such as the regulation of the inflammatory microenvironment, structural biomimicry, and cartilage regeneration are usually studied separately, while relatively little attention is paid to the continuous relationship between the inflammatory process and pathological angiogenesis, as well as the corresponding two-drug sequential delivery design.

[0011] To address the aforementioned issues, this paper presents a dual-drug nanocomposite particle, a hydrogel complex containing the nanocomposite particle, a tissue-engineered meniscus, a preparation method, and applications. Addressing the challenge of synergistic drug delivery, cell support, and reconstruction of damaged tissue structures during the repair of osteoarthritis-related meniscus injuries, this paper proposes a tissue-engineered meniscus construction scheme based on a dual-drug nanodelivery system, hydrogel, bone marrow mesenchymal stem cells, and a three-dimensional printed scaffold.

[0012] This application first constructs Sun@M-Lut dual-drug nanocomposite particles, comprising mesoporous silica nanoparticles, sunitinib, and luteolin. Sunitinib is loaded within the mesoporous channels of the mesoporous silica nanoparticles. The surface of the mesoporous silica nanoparticles is aminated, and luteolin forms Schiff base bonds with its surface amino groups. This results in sunitinib and luteolin being located respectively within the channels and on the surface of the mesoporous silica nanoparticles, forming a dual-drug nanocomposite structure with different drug loading sites. Further, the Sun@M-Lut is dispersed in an HC hydrogel system formed from o-nitrobenzyl alcohol-modified hyaluronic acid and chondroitin sulfate methacrylate, and mixed with bone marrow mesenchymal stem cells to form a composite hydrogel system containing the dual-drug nanocomposite particles and bone marrow mesenchymal stem cells.

[0013] Building upon this foundation, a polycaprolactone meniscus scaffold was constructed using bio-3D printing technology. Sun@M-Lut-loaded HC hydrogel was mixed with bone marrow mesenchymal stem cells and cast into the polycaprolactone meniscus scaffold, followed by photocrosslinking to form a Sun@M-Lut / HC-PCL+BMSC tissue-engineered meniscus. This combination of a dual-drug nanodelivery system, composite hydrogel, bone marrow mesenchymal stem cells, and a three-dimensional polycaprolactone scaffold allows the dual-drug nanoparticles and bone marrow mesenchymal stem cells to be jointly supported by the HC hydrogel and combined with the PCL meniscus scaffold to form a three-dimensional tissue-engineered meniscus.

[0014] This application constructs Sun@M-Lut dual-drug nanocomposite particles by setting sunitinib and luteolin at different positions on mesoporous silica nanoparticles. Furthermore, it combines these particles with HC hydrogel, bone marrow mesenchymal stem cells, and PCL meniscus scaffolds to achieve the synergistic construction of dual-drug nanoparticles, cells, hydrogels, and three-dimensional scaffolds in the same tissue engineering system. This provides an integrated technical solution for drug delivery, cell support, and tissue reconstruction in osteoarthritis-related meniscus injuries.

[0015] This application provides a dual-drug nanocomposite particle, comprising mesoporous silica nanoparticles, sunitinib, and luteolin; Sunitinib is loaded within the mesoporous channels of the mesoporous silica nanoparticles, and luteolin is attached to the surface of the mesoporous silica nanoparticles. Furthermore, luteolin is connected to the amino groups on the surface of the mesoporous silica nanoparticles via Schiff base bonds.

[0016] The technical concept of this application is based on the sequential pathological process following meniscus injury: "early inflammation and oxidative stress - pathological angiogenesis - inhibited cartilage regeneration." The loading sites, connection methods, and release methods of the two drugs are designed accordingly, ensuring that the drug release sequence matches the chronological relationship of the pathological process. Specifically, luteolin is placed on the surface of mesoporous silica nanoparticles and connected by Schiff base bonds, allowing for preferential release in an acidic pathological microenvironment for early inflammatory microenvironment regulation. Sunitinib is loaded inside the mesoporous channels, allowing for sustained release through diffusion after the aforementioned surface drug release, thus continuously regulating pathological angiogenesis. Therefore, the spatial position of the drug in the delivery system itself corresponds to the expected time stage of its action.

[0017] If luteolin and sunitinib are co-encapsulated or directly mixed in a hydrogel in the same manner, the two drugs will be unable to form a release hierarchy corresponding to the pathological process of meniscus injury, and may be released simultaneously after implantation. Sunitinib begins to exert its anti-angiogenic effect before early inflammation is adequately controlled, and its action environment is inconsistent with the subsequent stable hypo-angiogenic environment. Furthermore, the overlapping action times of luteolin and sunitinib are not conducive to forming a clear treatment process of "first anti-inflammatory, then regulation of pathological angiogenesis." Therefore, this application utilizes the hierarchical structure of the internal pores and particle surface of mesoporous silica to separately carry the two drugs, so that the carrier structure corresponds to the drug action sequence.

[0018] Optionally, the surface of the mesoporous silica nanoparticles is subjected to amylation treatment to form amino groups, and the luteolin forms Schiff base bonds with the amino groups.

[0019] Optionally, the average particle size of the dual-drug nanocomposite particles is 270±30 nm.

[0020] This application provides a method for preparing the above-mentioned dual-drug nanocomposite particles, comprising: Preparation of mesoporous silica nanoparticles; Sunitinib was loaded into the mesoporous channels of the mesoporous silica nanoparticles; Surface amination treatment was performed on mesoporous silica nanoparticles loaded with sunitinib. Luteolin is reacted with surface-aminated mesoporous silica nanoparticles to form Schiff base bonds between luteolin and the amino groups on the surface of the mesoporous silica nanoparticles, thus obtaining the dual-drug nanocomposite particles.

[0021] The sequence of preparation steps in this application corresponds to the spatial distribution and subsequent temporal release requirements of the two drugs: First, sunitinib is loaded into the mesoporous channels of mesoporous silica nanoparticles, forming a relatively closed internal drug storage region. Then, the particle surface is aminated, and luteolin is further bonded to the surface amino groups to form Schiff base bonds, placing luteolin on the outer layer of the particle. This creates a hierarchical structure of "sunitinib loaded in internal channels and luteolin attached to the outer surface." This structure allows the surface-attached luteolin to preferentially respond to the acidic environment of the lesion, while the sunitinib inside the channels continues to diffuse and release through the channels after the outer layer drug is released, thus forming a release sequence that matches the pathological process of meniscus injury. Therefore, the above preparation sequence is used to establish the spatial hierarchy of the two drugs within the nanoparticles; if the drug loading position is changed or the two drugs are loaded in the same way, it may be difficult to obtain the temporal release behavior that matches the pathological process.

[0022] Optionally, sunitinib can be loaded into the mesoporous channels of the mesoporous silica nanoparticles by ultrasonic treatment.

[0023] This application provides a hydrogel composite comprising a hydrogel matrix and the aforementioned dual-drug nanocomposite particles dispersed in the hydrogel matrix.

[0024] Optionally, the hydrogel matrix may also include bone marrow mesenchymal stem cells.

[0025] This application provides a method for preparing the above-mentioned hydrogel composite, characterized in that the hydrogel composite is obtained by photocrosslinking and curing of o-nitrobenzyl alcohol modified hyaluronic acid, chondroitin sulfate methacrylate, the above-mentioned dual-drug nanocomposite particles and photoinitiator.

[0026] This application provides the application of the above-mentioned dual-drug nanocomposite particles in the preparation of tissue-engineered menisci.

[0027] This application provides a tissue-engineered meniscus, including a meniscus scaffold and a hydrogel composite within the meniscus scaffold.

[0028] In this application, the HC hydrogel serves two purposes: firstly, as a cell encapsulation material, and secondly, in conjunction with the drug delivery mechanism of Sun@M-Lut nanoparticles. If Sun@M-Lut nanoparticles are placed directly within the joint cavity, the flow of synovial fluid may cause the nanoparticles to leave the meniscus defect site, thus shortening their effective duration of action in the lesion area. Furthermore, local aggregation or rapid loss of nanoparticles can also affect the stable implementation of the dual-drug sequential release in vivo. Therefore, this application further disperses Sun@M-Lut within the HC hydrogel network, enabling the HC hydrogel to provide local storage and diffusion inhibition for the nanoparticles. This reduces the loss of nanoparticles due to synovial fluid flushing while prolonging their residence time at the defect site, allowing the nanoparticles' pH-responsive release and pore diffusion release mechanisms to continue functioning within the joint cavity environment.

[0029] Moreover, Sun@M-Lut and HC hydrogel form a delivery relationship at different levels. Specifically, the Schiff base bonds within Sun@M-Lut determine whether luteolin dissociates from the nanoparticle surface, while the mesoporous channels provide storage space for the continuous diffusion of sunitinib. HC hydrogel primarily alters the diffusion pathways of nanoparticles and drugs into the external environment of the joint cavity, without changing the loading positions and connection methods of the two drugs within the nanoparticles. Therefore, the addition of HC hydrogel does not change the basic release sequence of preferential release of luteolin followed by sustained release of sunitinib. Instead, it can make this sequential release process more stable in the dynamic environment of the joint cavity by prolonging the residence time of nanoparticles in the defect area and increasing the resistance to outward diffusion of drugs. Thus, nanoparticles mainly undertake the functions of pathological microenvironment response and sequential release of two drugs, while HC hydrogel mainly undertakes the functions of local storage, cell carrying, and diffusion regulation. The two form a hierarchical synergy in function, rather than substituting for each other.

[0030] Optionally, the hydrogel matrix also includes bone marrow mesenchymal stem cells. In this application, BMSCs are added both as conventional seed cells in tissue engineering and as regenerative response cells after pathological microenvironment remodeling. The inflammatory and oxidative stress environment following meniscus injury is unfavorable for BMSC survival and chondrogenic differentiation. Therefore, the inflammatory and oxidative stress environment is first improved by releasing luteolin; on this basis, sunitinib is used to continuously regulate pathological angiogenesis, maintaining the hypovascular microenvironment required for meniscus regeneration, thereby providing suitable conditions for BMSCs to further differentiate into chondrocytes. Therefore, the dual-drug system creates conditions for BMSCs to exert their tissue regeneration function by sequentially improving the external microenvironment in which they reside.

[0031] Optionally, the meniscus scaffold is a scaffold formed with polycaprolactone using bio-3D printing technology.

[0032] Optionally, the meniscus support includes a mesh structure formed by printed filaments, and the hydrogel composite is disposed within the mesh structure.

[0033] In meniscus replacement surgery, the PCL scaffold serves two purposes: providing an external framework to support the hydrogel and bearing the primary mechanical load on the meniscus defect. The meniscus defect area is located within the joint cavity environment subjected to continuous flexion, extension, and compression. HC hydrogel alone cannot withstand the corresponding mechanical load for extended periods and may deform or break due to repeated compression, thus affecting the stable distribution of nanoparticles and drug release within the hydrogel. Therefore, this application utilizes 3D printing to form a porous PCL framework that matches the anatomical morphology of the meniscus defect. The PCL then bears the primary mechanical support function, while the HC hydrogel, located within the PCL framework, primarily undertakes cell support, nanoparticle storage, and local microenvironment regulation, thereby avoiding the hydrogel directly bearing the entire mechanical load.

[0034] Thus, the tissue-engineered meniscus of this application features a functional division among different materials: Sun@M-Lut is responsible for the time-series delivery of dual drugs according to the pathological microenvironment; HC hydrogel is responsible for storing nanoparticles at the defect site, carrying BMSCs, and regulating local drug diffusion; and the PCL scaffold is responsible for bearing the main mechanical load required for meniscus replacement. These three components correspond to three levels: pathological microenvironment regulation, local cell and drug delivery, and structural mechanical reconstruction, respectively, and form an overall tissue-engineered construct through spatial nesting.

[0035] This application provides a method for the above-mentioned tissue-engineered meniscus, including: The above-mentioned dual-drug nanocomposite particles were added to a hydrogel system formed by o-nitrobenzyl alcohol-modified hyaluronic acid and chondroitin sulfate methacrylate. Bone marrow mesenchymal stem cells were added to the hydrogel system and mixed. Polycaprolactone meniscus scaffolds were fabricated using bio-3D printing technology. The hydrogel mixture containing the dual-drug nanocomposite particles and bone marrow mesenchymal stem cells was cast into the polycaprolactone meniscus scaffold and photocrosslinked to obtain the tissue-engineered meniscus.

[0036] The beneficial effects of this application include, but are not limited to: 1. Based on the dual-drug nanocomposite particles, the hydrogel complex containing them, the tissue-engineered meniscus, the preparation method, and the application of this application, and considering the pathological characteristics of the early inflammation and oxidative stress in osteoarthritis-related meniscus injury being interconnected with subsequent pathological angiogenesis, luteolin and sunitinib are configured as dual-drug components with different spatial locations and release mechanisms. Luteolin is preferentially released to improve the early inflammatory and oxidative stress environment, while sunitinib is subsequently released continuously to regulate pathological angiogenesis. This ensures that the drug release sequence matches the pathological process after meniscus injury, rather than indiscriminately releasing drugs with different objectives simultaneously after implantation. This is beneficial for maintaining the hypovascular microenvironment required for meniscus regeneration after inflammation is controlled, providing suitable conditions for BMSC differentiation into chondrocytes.

[0037] 2. Based on the dual-drug nanocomposite particles, the hydrogel complex containing them, the tissue-engineered meniscus, the preparation method, and the application of this application, considering the need to sequentially address the inflammatory microenvironment and pathological angiogenesis issues in meniscus injury repair, luteolin and sunitinib are selected as regulatory components for the preceding and following stages, respectively. Luteolin is used to regulate the early inflammatory and oxidative stress environment, while sunitinib is used to continuously inhibit pathological angiogenesis. The two complement each other through different stages of action, enabling a continuous regulatory process of improving the inflammatory microenvironment and constructing a hypovascular microenvironment. Specifically, the resulting system possesses both anti-inflammatory and antioxidant effects. Luteolin targets TLR2 and its downstream scaffold protein TIFA, doubly inhibiting TLR2-TIFA-mediated inflammatory signal amplification; subsequently, sunitinib blocks the FLI1-VEGFA angiogenesis pathway, reconstructing the hypovascular microenvironment at the meniscus defect site, achieving a temporal regulatory hierarchy to jointly promote the differentiation and regeneration of BMSCs into chondrocytes.

[0038] 3. Based on the dual-drug nanocomposite particles, the hydrogel complex containing them, the tissue-engineered meniscus, the preparation method, and the application of this application, different drug loading regions are formed by the internal channels and particle surface of mesoporous silica nanoparticles. Sunitinib is placed inside the mesoporous channels, and luteolin is linked to the particle surface through Schiff base bonds, so that the spatial positions of the two drugs correspond to the expected release sequence. This hierarchical loading method allows the drug release sequence to be determined by the spatial structure of the nanoparticles themselves, rather than relying on external artificial control of the dosing time, thus making it suitable for the continuously changing joint cavity environment of the local pathological microenvironment after meniscus injury.

[0039] 4. Based on the dual-drug nanocomposite particles, the hydrogel complex containing them, the tissue-engineered meniscus, the preparation method, and the application of this application, Sun@M-Lut is further dispersed in an HC hydrogel formed by HANB / CSMA. This allows the hydrogel to not only bear the burden of BMSC cells and act as a biomimetic component of the cartilage matrix, but also to form a local storage and diffusion regulation effect on the nanoparticles. This reduces the loss of nanoparticles caused by synovial fluid flushing in the joint cavity and prolongs the action time of the nanoparticles at the meniscus defect site. At the same time, a layered functional relationship is formed between the nanoparticles and the hydrogel, which improves the in vivo delivery stability without changing the dual-drug loading mode inside the nanoparticles.

[0040] 5. Based on the dual-drug nanocomposite particles, the hydrogel complex containing them, the tissue-engineered meniscus, the preparation method, and the application of this application, a structure combining a PCL three-dimensional scaffold and an HC hydrogel is adopted. The PCL mainly undertakes the mechanical support and defect space maintenance after meniscus replacement, while the HC hydrogel mainly undertakes the role of cell and nanoparticle support and local microenvironment regulation. This avoids relying solely on the hydrogel to bear the mechanical load required for meniscus replacement and reduces the adverse effects of hydrogel mechanical damage on the stable release of nanoparticles, thereby achieving synergy between pathological microenvironment regulation, cell regeneration, and structural mechanical reconstruction.

[0041] 6. Based on the dual-drug nanocomposite particles, the hydrogel complex containing them, the tissue-engineered meniscus, the preparation method, and the application of this application, the biomimetic tissue-engineered meniscus Sun@M-Lut / HC-PCL constructed by combining PCL scaffolds can achieve the reconstruction of meniscus structure and function within the knee joint. Under the induction of Sun@M-Lut, BMSCs differentiate into chondrocytes and highly express related cartilage regeneration genes. Attached Figure Description

[0042] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 Transmission electron microscopy (TEM) images of the mesoporous silicon nanoparticles MSN, Sun@MSN, MSN-Lut, and Sun@M-Lut involved in Example 4 of this application.

[0043] Figure 2 The average particle size statistics for MSN, Sun@MSN, MSN-Lut, and Sun@M-Lut involved in Example 4 of this application are presented.

[0044] Figure 3 Zeta potential analysis of different nanoparticles involved in Example 4 of this application.

[0045] Figure 4 This is an element distribution mapping diagram of Sun@M-Lut involved in Embodiment 4 of this application.

[0046] Figure 5 This is the energy spectrum of Sun@M-Lut involved in Embodiment 4 of this application.

[0047] Figure 6 The X-ray photoelectron spectra of C1s, N1s, and F1s for each group of MSN, Sun@MSN, MSN-Lut, and Sun@M-Lut involved in Embodiment 4 of this application are shown.

[0048] Figure 7 The Fourier transform infrared spectra of MSN, Sun@MSN, MSN-Lut, and Sun@M-Lut involved in Embodiment 4 of this application are shown.

[0049] Figure 8 The results are the nuclear magnetic resonance characterization results of Sun@MSN, MSN-Lut and Sun@M-Lut involved in Embodiment 4 of this application.

[0050] Figure 9 This is the cumulative release curve of luteolin in Sun@M-Lut under different pH conditions, which was quantitatively determined by high performance liquid chromatography at a wavelength of 329 nm, according to Example 4 of this application.

[0051] Figure 10 This is the cumulative release curve of sunitinib in Sun@M-Lut under different pH conditions, which was quantitatively determined using an ultraviolet spectrophotometer according to Example 4 of this application.

[0052] Figure 11 The CSMA and HANB hydrogels involved in Example 5 of this application were crosslinked with 365 nm ultraviolet light to obtain HC and Sun@M-Lut / HC hydrogels.

[0053] Figure 12 The scanning electron microscope (SEM) images, pore size analysis, and porosity analysis of the HC and Sun@M-Lut / HC hydrogels involved in Example 5 of this application are shown.

[0054] Figure 13 This is a statistical graph (10 cycles) of compression cycling tests of Sun@M-Lut / HC hydrogels with different drug loading amounts involved in Example 5 of this application.

[0055] Figure 14 The compression stress-strain curves of the HC and Sun@M-Lut / HC hydrogels involved in Example 5 of this application are shown.

[0056] Figure 15The tensile stress-strain curves of the HC and Sun@M-Lut / HC hydrogels involved in Example 5 of this application are shown.

[0057] Figure 16 The image shows the dynamic amplitude scanning curves of the HC and Sun@M-Lut / HC hydrogels involved in Example 5 of this application.

[0058] Figure 17 This document presents the in vitro degradation behavior and statistical analysis of HC and Sun@M-Lut / HC hydrogels involved in Example 5 of this application.

[0059] Figure 18 This document presents the in vitro swelling behavior of HC and Sun@M-Lut / HC hydrogels involved in Example 5 of this application, and the corresponding statistical analysis thereof.

[0060] Figure 19 This is the result of live / dead staining of cells co-cultured with Sun@M-Lut / HC hydrogel in Example 5 of this application.

[0061] Figure 20 This refers to the hemolysis experiment conducted using HC and Sun@M-Lut / HC hydrogel extract in Example 5 of this application.

[0062] Figure 21 Example 6 of this application describes the use of the CCK-8 assay to detect the biocompatibility of RAW 264.7 macrophages with bone marrow mesenchymal stem cells (BMSCs).

[0063] Figure 22 This refers to the immunofluorescence staining and corresponding quantitative analysis of CD86 (M1 type marker) and CD206 (M2 type marker) in macrophages after LPS induction and treatment with MSNs, Sun@MSN, MSN-Lut, and Sun@M-Lut, as described in Example 6 of this application.

[0064] Figure 23 This is a flow cytometry analysis of the phenotypic polarization of macrophages M1 and M2 after LPS induction and treatment with MSNs, Sun@MSN, MSN-Lut, and Sun@M-Lut, as described in Example 6 of this application.

[0065] Figure 24 This refers to the relative gene expression levels of pro-inflammatory and anti-inflammatory cytokines in RAW 264.7 cells after LPS induction and treatment with MSNs, Sun@MSN, MSN-Lut, and Sun@M-Lut, as described in Example 6 of this application.

[0066] Figure 25 This is a Western blot analysis of the expression of inflammation-related cytokine proteins after different treatments involved in Example 6 of this application.

[0067] Figure 26 Example 6 of this application describes the evaluation of the antioxidant activity of each treatment group (MSNs, Sun@MSN, MSN-Lut, and Sun@M-Lut) using DPPH and ABTS free radical scavenging experiments.

[0068] Figure 27 Example 6 of this application describes the qRT-PCR detection of the mRNA expression levels of antioxidant genes SOD1, GPX1, and CAT in different treatment groups after hydrogen peroxide stimulation.

[0069] Figure 28 These are representative images of the DCFH-DA staining detection of intracellular reactive oxygen species levels in each group, as described in Example 6 of this application.

[0070] Figure 29 The enzyme activities of antioxidant enzymes SOD and GPX in different treatment groups involved in Example 6 of this application are shown.

[0071] Figure 30 These are representative fluorescence images of DHE and HPF levels in different treatment groups under oxidative stress conditions as described in Example 6 of this application.

[0072] Figure 31 This provides representative fluorescence images of angiogenesis and quantitative analysis of the total tubular structure length in the MSNs, Sun@MSN, MSN-Lut, and Sun@M-Lut treatment groups involved in Example 7 of this application.

[0073] Figure 32 This is a schematic diagram of the Transwell migration experiment and a representative image of crystal violet staining involved in Example 7 of this application.

[0074] Figure 33 This is a quantitative analysis of the number and migration rate of migrating cells in the Transwell migration experiment involved in Example 7 of this application.

[0075] Figure 34 The relative gene expression levels of vascular endothelial growth factor A (VEGFA) in each treatment group involved in Example 7 of this application (n=3).

[0076] Figure 35 Western blot analysis of the expression of VEGFA, SOX9, agglutinin (ACAN), type I collagen (COL Ⅰ) and type II collagen (COL Ⅱ) proteins after different treatments as described in Example 7 of this application.

[0077] Figure 36These are Alsin blue staining images of the MSNs, Sun@MSN, MSN-Lut, and Sun@M-Lut processing groups involved in Embodiment 7 of this application.

[0078] Figure 37 This is a schematic diagram of the timeline of the nude mouse experiment involved in Embodiment 8 of this application.

[0079] Figure 38 This is the general appearance of the MSNs / HC-PCL and Sun@M-Lut / HC-PCL brackets involved in Embodiment 8 of this application.

[0080] Figure 39 This describes the subcutaneous implantation process of the MSNs / HC-PCL and Sun@M-Lut / HC-PCL stents involved in Embodiment 8 of this application.

[0081] Figure 40 This is a gross photograph of mice 8 weeks after implantation of the HC-PCL, MSNs / HC-PCL, and Sun@M-Lut / HC-PCL scaffolds involved in Example 8 of this application.

[0082] Figure 41 Immunohistochemical images of HE, SO, VEGFA, and COL II, as well as α-SMA fluorescence staining images and statistical data, and Young's modulus statistics of the HC-PCL, MSNs / HC-PCL, and Sun@M-Lut / HC-PCL stents involved in Example 8 of this application after 8 weeks.

[0083] Figure 42 The relative gene expression levels of COL Ⅰ, COL Ⅱ, ACAN and SOX9 in each treatment group involved in Example 8 of this application (n=3).

[0084] Figure 43 This is a KEGG pathway enrichment analysis of the signaling pathways that have undergone significant changes, as described in Example 9 of this application.

[0085] Figure 44 This is a heatmap of key differentially expressed genes involved in inflammation, oxidative stress, angiogenesis, and chondrogenic differentiation in the control group, lipopolysaccharide-induced group, and LPS+Sun@M-Lut group involved in Example 9 of this application.

[0086] Figure 45 This study analyzes the molecular docking and interaction between luteolin and sunitinib and the target protein involved in Example 9 of this application.

[0087] Figure 46 This is a schematic diagram of the experimental process of implanting a Sun@M-Lut / HC-PCL scaffold for replacement repair after constructing an osteoarthritis model, as described in Embodiment 10 of this application.

[0088] Figure 47 This is the general appearance of the 3D printed Sun@M-Lut / HC-PCL scaffold involved in Embodiment 10 of this application.

[0089] Figure 48 This is the surgical procedure for implanting a crescent-shaped stent into a medial meniscus defect model of a New Zealand white rabbit, as described in Embodiment 10 of this application.

[0090] Figure 49 The results of magnetic resonance imaging evaluation of the knee joint at 12 weeks in the control group, osteoarthritis group, MSNs / HC-PCL group and Sun@M-Lut / HC-PCL group involved in Example 10 of this application are shown.

[0091] Figure 50 This is an image of a 12-week-old New Zealand rabbit footprint related to Embodiment 10 of this application.

[0092] Figure 51 This is a quantitative analysis of the gait imprint stride length of the New Zealand rabbit involved in Example 10 of this application.

[0093] Figure 52 This is a gross morphological assessment of the regenerated meniscus and articular cartilage surface 12 weeks after implantation in the control group, MSNs / HC-PCL group, and Sun@M-Lut / HC-PCL group involved in Example 10 of this application.

[0094] Figure 53 The results of hematoxylin-eosin staining and safranin O staining are shown for the MSNs / HC-PCL group and Sun@M-Lut / HC-PCL group involved in Example 10 of this application.

[0095] Figure 54 The images show the histological staining results of COL II and COL I, as well as the immunofluorescence staining results of VEGFA and TNF-α, for the MSNs / HC-PCL group and the Sun@M-Lut / HC-PCL group involved in Example 10 of this application.

[0096] Figure 55 The International Society for Cartilage Repair score is given 12 weeks after implantation in Example 10 of this application. Detailed Implementation

[0097] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments. Unless otherwise specified, the raw materials and reagents in the embodiments of the present application are all purchased through commercial channels.

[0098] The mesoporous silica nanoparticles described herein refer to particulate materials that are primarily composed of silica or silica-containing inorganic silicon materials, possess a mesoporous structure, and have at least one size at the nanoscale. Mesoporous silica nanoparticles may also be referred to as mesoporous silica nanoparticles, mesoporous silica nanocarriers, mesoporous silica nanomaterials, or mesoporous silica nanocarriers. Mesoporous silica nanoparticles possess a porous structure surrounded by a silica framework, including interconnected or partially interconnected mesoporous channels, which can be used to accommodate, adsorb, or load drug molecules. The morphology of mesoporous silica nanoparticles can be spherical, near-spherical, ellipsoidal, rod-shaped, or other particle morphologies capable of forming a mesoporous structure. Mesoporous silica nanoparticles can utilize mesoporous silica materials known in the art, including but not limited to MCM series mesoporous silica, SBA series mesoporous silica, and other silica nanoparticles with mesoporous structures. The particle size, pore size, pore volume, specific surface area, and pore structure of mesoporous silica nanoparticles can be adjusted according to the required drug loading and release performance. In this application, mesoporous silica nanoparticles serve as inorganic nanocarriers for dual-drug nanocomposite particles. Sunitinib is primarily loaded within the mesoporous channels of the mesoporous silica nanoparticles, while luteolin is attached to the surface of the mesoporous silica nanoparticles, thereby forming a nanocomposite structure with different drug spatial loading positions. This structure corresponds to the dual-drug delivery system described in this application.

[0099] The mesoporous channels described herein refer to the mesoporous-scale pores formed within or penetrating the mesoporous silica framework, and the interconnected channel structures they form. They can also be referred to as mesopores, mesoporous channels, mesoporous networks, pore structures, or mesoporous nanopores. Mesoporous channels provide space for drug molecules, allowing them to enter and distribute within the mesoporous silica nanoparticles through physical adsorption, diffusion within the channels, filling within the channels, or other non-covalent interactions. Mesoporous channels can be regularly arranged or irregular or interconnected networks. In this application, sunitinib loading within mesoporous channels means that sunitinib is at least partially located within the channels of the mesoporous silica nanoparticles, without requiring sunitinib to be covalently bonded to the silica framework. Sunitinib can be distributed within the channels, on the surface of the channel walls, or in the pore spaces formed within the channels, and can diffuse and be released from the channels to the external medium during use. Loading within mesoporous channels should not be limited to a specific loading mechanism, channel arrangement, or drug distribution within the channels. As long as sunitinib is at least partially located within the mesoporous structure of the mesoporous silica nanoparticles, it can be considered a mesoporous channel loading method as described in this application.

[0100] The surface amination treatment described herein refers to the introduction of amino-functionalized chemical groups onto the outer surface and / or inner surface of mesoporous silica nanoparticles through chemical modification, surface grafting, silanization, or other methods known in the art, thereby giving the surface of the mesoporous silica nanoparticles amino groups that can participate in subsequent chemical reactions. Surface amination treatment can employ aminosilane coupling agents to silanize the mesoporous silica nanoparticles. Aminosilane coupling agents include, but are not limited to, 3-aminopropyltrimethoxysilane (APS), 3-aminopropyltriethoxysilane (APTES), and other silane compounds capable of undergoing condensation or grafting reactions with hydroxyl groups on the silica surface to introduce amino groups. The amino groups can exist as primary amino groups, secondary amino groups, or other nitrogen-containing functional groups capable of undergoing condensation reactions with carbonyl-containing compounds. The amino groups can be distributed on the outer surface of the mesoporous silica nanoparticles, the inner wall of the mesoporous channels, or both, and the degree of amination can be adjusted according to the requirements of subsequent drug conjugation. In this application, surface amination is used to introduce amino groups onto the surface of mesoporous silica nanoparticles, enabling luteolin to undergo a condensation reaction with the amino groups and form Schiff base bonds. The current method specifically uses APS to perform surface amination treatment on the mesoporous silica microspheres. Surface amination treatment should not be construed as limited to APS as a single reagent or to a specific processing method; any treatment that can form amino groups on the surface of mesoporous silica nanoparticles that can chemically bond with luteolin falls under the scope of surface amination treatment described in this application.

[0101] The hydrogel matrix described herein refers to a gel-like continuous phase material capable of absorbing and retaining moisture, formed by a three-dimensional network structure of hydrophilic polymeric materials through physical action, chemical cross-linking, or a combination thereof. The hydrogel matrix can be formed from one or more natural polymers, synthetic polymers, natural polymer-modified materials, and / or synthetic polymer-modified materials. The hydrogel matrix can be formed through physical cross-linking, ionic cross-linking, chemical cross-linking, photocross-linking, enzymatic cross-linking, or other methods known in the art. The hydrogel matrix can serve as a carrier medium for nanoparticles, drugs, cells, or other bioactive components, allowing the components to be at least partially dispersed, embedded, or fixed within the three-dimensional network structure of the hydrogel. Simultaneously, the hydrogel matrix can possess certain water content, viscoelasticity, and three-dimensional spatial stability to be suitable for forming localized tissue engineering materials. In this application, the hydrogel matrix is ​​specifically an HC hydrogel formed from o-nitrobenzyl alcohol-modified hyaluronic acid (HANB) and chondroitin sulfate methacrylate (CSMA), used to carry dual-drug nanocomposite particles and bone marrow mesenchymal stem cells. In this application, the hydrogel matrix is ​​a general term for the function and structural state of the material and should not be limited to a specific combination of HANB and CSMA. Other hydrogel materials that can form a three-dimensional hydrogel network and carry the dual-drug nanocomposite particles can also be used as the hydrogel matrix without changing the technical concept of this application.

[0102] The photocrosslinking-cured hydrogels described in this article refer to the crosslinking reaction that occurs in the hydrogel precursor system under light irradiation, causing the crosslinkable groups to form a crosslinked network, thereby transforming it from a liquid or flowable state into a gel state with a certain shape retention capability and a three-dimensional network structure. Photocrosslinking curing can be achieved using ultraviolet light, visible light, or other light sources capable of initiating the corresponding photocrosslinking reaction. The appropriate photoinitiation system and irradiation conditions can be selected based on the polymerizable or crosslinkable groups contained in the hydrogel precursor material. Crosslinkable groups include, but are not limited to, methacrylate groups, acrylate groups, vinyl groups, and other functional groups capable of polymerization or crosslinking under light irradiation. Photocrosslinking can form covalent crosslinked networks or, together with other crosslinking methods, form composite crosslinked networks. The curing described in this article refers to the process of increasing the degree of crosslinking in the hydrogel precursor system and forming a stable gel structure through light irradiation, and is not limited to a fully crosslinked or fully transformed state. In this application, HANB and CSMA constitute a hydrogel precursor system, wherein CSMA has photocrosslinking ability after being modified by methacrylate esterification, and the hydrogel precursor system forms HC hydrogel after being irradiated with light; further, the hydrogel loaded with dual-drug nanocomposite particles is mixed with bone marrow mesenchymal stem cells and cast into a polycaprolactone meniscus scaffold for photocrosslinking to form a tissue-engineered meniscus.

[0103] To meet the needs of the prior art, this application provides a Sun@M-Lut / HC drug delivery system, which can release Sun@M-Lut in the acidic microenvironment (pH<7) of osteoarthritis by responsively degrading HC hydrogel. The Schiff base bond connecting luteolin and MSNs is responsively broken to release luteolin to correct early inflammation. Then, sunitinib encapsulated in the pores of MSNs is slowly released to regulate angiogenesis. This time-sequential drug release provides a stable microenvironment for the differentiation of BMSCs into chondrocytes under OA conditions.

[0104] To reshape the pathological microenvironment of osteoarthritis and regulate early intra-articular inflammation in accordance with the disease progression, this treatment plan selects luteolin, a natural flavonoid traditional Chinese medicine, which possesses anti-inflammatory, antibacterial, antiviral, and antitumor activities. Previous studies have shown that luteolin inhibits IL-1β-induced chondrocyte inflammation and alleviates osteoarthritis. Secondly, to address the obstacle of angiogenesis to cartilage regeneration at the meniscus injury site, as newly formed blood vessels disrupt the original avascular microenvironment of cartilage, leading to a decrease in the ability of cartilage to synthesize type II collagen, vascular signaling factors (VEGF, BMP-2) can induce chondrocytes to differentiate into osteoblasts or fibroblasts, synthesizing type I collagen, ultimately forming fibrochondrocytes or intrachondral ossification, resulting in the loss of the mechanical function of normal hyaline cartilage. Therefore, sunitinib was chosen as a multi-target tyrosine kinase inhibitor that can precisely inhibit vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor (PDGFR), etc., blocking the signaling pathways of angiogenesis from the source. This mechanism has been proven to effectively inhibit angiogenesis in tumor treatment.

[0105] In the construction of the drug delivery system, an exfoliated carrier system based on mesoporous silica nanoparticles was developed. Utilizing the mesoporous channels and surface grafting hierarchical structure, a two-drug sequential delivery strategy was employed. The Schiff base bonds connecting the outer layer of luteolin and the mesoporous silica undergo pH-responsive cleavage, achieving rapid release to inhibit early inflammation. Sunitinib, encapsulated within the channels, is released slowly to regulate angiogenesis, creating a stable hypovascular microenvironment that promotes the differentiation of bone marrow stem cells (BMSCs) into cartilage, thus achieving meniscus cartilage regeneration. This temporal and spatial difference in drug delivery enables the system to achieve sequential delivery, unifying the treatment sequence with the course of meniscus injury.

[0106] Furthermore, to achieve structural and functional reconstruction of meniscus defects, a three-dimensional scaffold with sufficient mechanical strength is needed to support the nanocarriers and seed cells. Combining hydrogel and 3D printing technologies, Sun@M-Lut and BMSCs are loaded into a photocrosslinked hydrogel system composed of o-nitrobenzyl alcohol-modified hyaluronic acid (HANB) and chondroitin sulfate methacrylate (CSMA). Unlike the simple mixing in Chinese patent application CN122272631A, in this application, chondroitin sulfate is the main component of the cartilage matrix, and methacrylate modification endows it with photocrosslinking ability, which can rapidly form a stable three-dimensional network structure under ultraviolet (UV) irradiation. Hyaluronic acid is widely known for its excellent water retention capacity and viscoelasticity. After o-nitrobenzyl modification of hyaluronic acid to obtain HANB, HANB retains its inherent biological activity and introduces photosensitive groups. Under 365 nm ultraviolet light irradiation, the o-nitrobenzyl group undergoes photolysis to generate an aldehyde group. The aldehyde group can react with the primary amino group of the adjacent HANB chain to form a Schiff base bond, thereby constructing a dynamically cross-linked hydrogel with pH-sensitive cleavage characteristics, further enhancing the pH responsiveness of the drug delivery system. Furthermore, it is combined with a 3D-printed crescent-shaped PCL scaffold to construct Sun@M-Lut / HC-PCL, achieving stable release of the material within the joint cavity and providing certain shock absorption and cushioning effects, which aligns with the function of the meniscus in the knee joint.

[0107] Furthermore, this application's protocol, through transcriptome sequencing, clearly demonstrated that Sun@M-Lut / HC promotes meniscus cartilage regeneration by remodeling the pathological microenvironment of osteoarthritis through the TLR2-HIF-1α-TGF-β pathway. Molecular docking results confirmed that luteolin can stably bind to the extracellular domain of the TLR2 protein (binding free energy -8.0 kcal / mol) and simultaneously target the downstream adaptor protein TIFA (binding free energy -6.0 kcal / mol), suggesting that luteolin can directly target the TLR2-TIFA signaling complex, blocking TLR2 receptor-mediated inflammatory signal transduction. Sunitinib, on the other hand, effectively binds to VEGFA (binding free energy -7.2 kcal / mol) and FLI1 (binding free energy -6.6 kcal / mol), exerting an anti-angiogenic effect.

[0108] To verify its in situ meniscus regeneration capacity, a New Zealand rabbit osteoarthritis model was constructed for meniscus replacement. Sun@M-Lut / HC-PCL was implanted into the rabbit knee joint. After 12 weeks, the rabbits regained their walking ability, and there was no swelling, fever, or other inflammatory response on the knee joint surface. Immunohistochemistry and immunofluorescence analysis after tissue harvesting showed that inflammatory factors and angiogenesis factors were downregulated, while chondrocyte growth factor was significantly upregulated, further confirming the feasibility of Sun@M-Lut / HC for meniscus cartilage regeneration under OA conditions.

[0109] This application further provides a method for preparing nanoparticles for repairing the meniscus, including the following steps: 1) Synthesis of mesoporous silica microspheres (MSNs); 2) Synthesis of sunitinib-loaded mesoporous silica microspheres (Sun@MSN): MSNs microspheres were dispersed in PBS, and sunitinib was loaded into the mesoporous channels by sonication. 3) Preparation of surface-aminated mesoporous silica microspheres (MSN-NH2): MSNs microspheres were dispersed in deionized water, APS (3-aminopropyltrimethoxysilane) was added, and the mixture was stirred overnight at room temperature. After stirring, the mixture was centrifuged to remove unreacted substances, and aminated mesoporous silica microspheres (MSN-NH2) were obtained. 4) Preparation of luteolin-loaded surface-aminated mesoporous silica microspheres (Sun@M-Lut): MSN-NH2 was dispersed in deionized water, luteolin powder was added, and the mixture was shaken in an ice bath to ensure the dispersion and dissolution of luteolin. Subsequently, the solution was transferred to room temperature and stirred overnight to ensure successful grafting of luteolin to mesoporous silica, resulting in Sun@M-Lut loaded with luteolin.

[0110] This application further provides a hydrogel material for meniscus repair, comprising o-nitrobenzyl alcohol-modified hyaluronic acid (HANB) and chondroitin sulfate methacrylate (CSMA) photocrosslinked to form an HC hydrogel loaded with bone marrow stem mesenchymal stem cells (BMSCs) and Sun@M-Lut nanoparticles for regulating the pathological microenvironment, constructing a Sun@M-Lut / HC delivery system. The concentration of CSMA is 8% w / v, the concentration of HANB is 2% w / v, and the final concentration of the nanoparticles for meniscus repair is 20 ug / mL. This delivery system is encapsulated in a 3D-printed PCL scaffold to provide mechanical support, forming a "reinforced concrete" structure. Implanted in a New Zealand rabbit osteoarthritis model, 12 weeks after replacement surgery, Sun@M-Lut / HC can responsively correct early inflammation, thereby slowly regulating angiogenesis and creating a stable hypovascular microenvironment for meniscus cartilage regeneration, simultaneously achieving meniscus structural and functional reconstruction.

[0111] The present application solution will be described below through specific embodiments.

[0112] Example 1: Construction and Characterization of Sun@M-Lut Smart Response pH Nanoparticle Sustained-Release System 1) Preparation of Sun@M-Lut 20 mg of sunitinib was dissolved in 5 mL of water, and 35.7 mL of ethanol and 0.785 mL of ammonia were added. The mixture was stirred at room temperature for 5–10 min, followed by the addition of 1 mL of tetraethyl orthosilicate (TEOS). After stirring at room temperature for 1 h, the mixture was centrifuged at 10,000 rpm for 20 min and washed three times with ethanol to obtain dSiO2 silicon spheres. 4 g of hexadecyltrimethylammonium chloride (CTAC) was dissolved in 40 mL of water, and 400 μL of triethanolamine (TEA) was added. The mixture was stirred at room temperature for 1 h, followed by the addition of the aforementioned 20 mL dSiO2 aqueous solution. The mixture was stirred at 80 °C for another 1 h, and 300 μL of TEOS was gradually added dropwise. After cooling to room temperature, 1272 mg of Na2CO3 was added for etching for 30 min. The spheres were then washed three times with water, 1% NaCl-methanol solution, and anhydrous ethanol to obtain Sun@MSN microspheres. 200 mg of Sun@MSN microspheres and 200 μL of APS (3-aminopropyltrimethoxysilane) were dissolved in 5 mL of PBS and reacted overnight at room temperature to complete the amino modification. The mixture was centrifuged at 10,000 rpm for 20 minutes to separate the supernatant and precipitate. After lyophilization, the collected solid was Sun@M-NH2. 100 mg of Sun@M-NH2 was added to 10 mL of PBS and 100 mg of luteolin, and the reaction was continued overnight at room temperature or 4°C, linked by Schiff base bonds. The white powder collected after centrifugation and lyophilization was Sun@M-Lut. After sonication, centrifugation, and lyophilization, the collected solid was the expected pH-responsive nanoparticle Sun@M-Lut.

[0113] 2) Material characterization of Sun@M-Lut The synthesized Sun@M-Lut was characterized, including scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to observe the morphology and size of the material; a nanoparticle size zeta potential analyzer was used to collect and analyze particle size data; solid-state NMR, XPS, and Fourier transform infrared spectroscopy were used to confirm the structure of Sun@M-Lut and whether the drug loading was successful. Simultaneously, the biocompatibility of the Sun@M-Lut nanoparticles was assessed using CCK-8 cytotoxicity assays.

[0114] 3) Detecting the intelligent pH-controlled release effect of Sun@M-Lut mesoporous silica nanoparticles for drug delivery First, the release amounts of sunitinib and luteolin were detected by UV spectrophotometer and HPLC to determine the wavelengths of their respective maximum absorption peaks. Then, the release amounts of sunitinib and luteolin in Sun@M-Lut were detected under different pH conditions (pH=6.0 and pH=7.4) and the relevant release rates were calculated.

[0115] Example 2: Cellular-level detection of the mechanism by which Sun@M-Lut regulates the cartilage immune microenvironment To verify the biological functions of Sun@M-Lut, including anti-inflammatory, angiogenesis-regulating, and cartilage regeneration-promoting effects, the extract of Sun@M-Lut was first collected. The main experimental methods used are as follows: 1) In vitro anti-inflammatory level detection RAW 264.7 cells were seeded into 6-well plates and stimulated with 100 ng / mL LPS to induce oxidative stress. After treatment with Sun@M-Lut extract for 24 h, immunofluorescence staining was performed to detect the expression of CD86 (M1 surface marker) and CD206 (M2 surface marker) proteins. Macrophage slides were fixed with 4% paraformaldehyde. Blocking with 5% bovine serum albumin at room temperature for 1 h, followed by incubation with primary antibody at 4°C overnight in a humidified chamber. After thorough washing with PBST, the slides were incubated with the corresponding fluorescently labeled secondary antibody at room temperature in the dark for 1 h. Cell nuclei were counterstained with DAPI, and slides were mounted with anti-fluorescence quenching mounting medium. Fluorescence images were acquired using a laser confocal microscope, and the average fluorescence intensity of CD86 in each group was analyzed using Image-J software. Simultaneously, qRT-PCR and Western blot experiments were used to detect the expression levels of inflammatory genes (TNF-α, IL-1β, and IL-10, etc.). The overall results were used to evaluate the macrophage polarization effect of Sun@M-Lut.

[0116] 2) Analysis of in vitro angiogenesis inhibition capacity HUVECs were seeded into 6-well plates, and the drug was added 24 h later. The cell migration-promoting ability was assessed using scratch and tube formation assays, and the pro-angiogenic level was then detected. Subsequently, the expression of intracellular angiogenic factors (VEGFAs) was detected using qRT-PCR and Western blot. The migration ability of HUVECs seeded in Transwell chambers after drug administration was then observed. These results were used to evaluate the inhibitory effect of Sun@M-Lut on angiogenesis.

[0117] 3) Chondrogenic capacity test After culturing BMSCs for 14 days following drug administration, Alsin Blue staining was performed, and the chondrogenic differentiation capacity was assessed based on the staining intensity. Subsequently, the expression levels of relevant chondrogenic genes (SOX9, COL II, COL I) in BMSCs were detected by qRT-PCR and Western Blot to assess the ability of Sun@M-Lut to promote chondrogenic regeneration.

[0118] Example 3: Demonstrating the effect of Sun@M-Lut tissue-engineered meniscus on cartilage regeneration in meniscus replacement in rabbits with osteoarthritis. 1) Preparation and characterization of cartilage-specific matrix biomimetic hydrogels First, HC hydrogel solution was prepared by dissolving 20 mg of HANB and 80 mg of CSMA in 1 mL of PBS. Then, Sun@M-Lut nanoparticles were added to the HC hydrogel, and 1% LAP was added to enable photocrosslinking and curing at 365 nm. Subsequently, a series of material characterizations were performed (SEM observation of morphology, rheological analysis, mechanical testing, and swelling rate detection). BMSCs were then mixed into the hydrogel, and both were co-cultured. Live / Dead staining was performed on the hydrogel sustained-release system at 1, 4, and 7 days of culture to determine its effect on cell proliferation.

[0119] 2) Construction of PCL meniscus scaffolds using bio-3D printing technology To construct a high-strength meniscus graft loaded with Sun@M-Lut / HC hydrogel, this approach combines bio-3D printing technology with a high-temperature nozzle to print a PCL frame to provide mechanical support. Key parameters such as the distribution and arrangement of the PCL frame, wire thickness, wire spacing, and mesh aperture size are used to simultaneously meet the functional requirements of internal mechanical support and cartilage regeneration.

[0120] 3) Verify the feasibility of using Sun@M-Lut tissue-engineered meniscus to repair inflamed meniscus injuries. First, type II collagenase was injected into the rabbit joints every 3 days. After 2 weeks of injection, joint fluid was extracted and the pH was measured to determine whether it was weakly acidic, which was a preliminary test to see if it caused inflammation. Then, the degree of redness and swelling on the surface and the walking posture were observed to confirm that the model was successfully established.

[0121] A tissue-engineered meniscus was constructed by casting a mixture of Sun@M-Lut-loaded HC hydrogel and BMSCs onto a PCL meniscus scaffold (Sun@M-Lut / HC-PCL+BMSC). To evaluate its meniscus regeneration effect, the constructed meniscus graft was replaced with its medial meniscus, and the regeneration effect was verified in vivo. Solid-state MRI was performed at 6 and 12 weeks postoperatively to assess the regeneration effect. Simultaneously, histological staining (HE, SO, COL II, and COL I), mechanical property testing, and immunohistochemical experiments (SOX9, α-SMA, VEGF, TNF-α) were conducted on the meniscus graft to systematically evaluate its potential to regulate the cartilage immune microenvironment and promote chondrogenesis.

[0122] Example 4 To regulate the acidic microenvironment (pH < 7) of osteoarthritis lesions in damaged menisci and achieve functional cartilage regeneration, this application designs a pH-sensitive, time-sensitive dual-drug delivery system (Sun@M-Lut) based on the inflammatory response and pathological angiogenesis during meniscus repair. Figure 1As shown, all nanocarrier groups exhibited a uniform spherical morphology under transmission electron microscopy. After grafting luteolin, a distinct organic coating layer appeared on the particle surface; the hydrodynamic particle size of the original mesoporous silica nanoparticles (MSNs) was 230±23.11 nm, while the hydrodynamic particle size of Sun@M-Lut increased to 270±28.72 nm. Figure 2 Preliminary evidence indicates successful dual-drug loading. Zeta potential analysis ( Figure 3 Further analysis revealed that the mesoporous silica nanoparticles exhibited a strong negative charge (-38±0.5 mV) due to the presence of numerous silanol groups (-Si-OH); after loading sunitinib, its tertiary amine groups could partially neutralize this negative charge. Notably, the zeta potential measured by Sun@M-Lut was -26±0.6 mV, confirming the successful grafting of luteolin onto the amino-modified mesoporous silica nanoparticle surface. To further verify the compositional integrity and spatial homogeneity of Sun@M-Lut, elemental mapping (… Figure 4 Combined with energy-dispersive X-ray spectroscopy, all five characteristic elements (silicon, oxygen, carbon, nitrogen, and fluorine) were detected. These elements were uniformly distributed within the nanoparticles, without localized enrichment, demonstrating that the two drugs achieved uniform co-distribution. Based on the energy dispersive X-ray spectroscopy (EDS) spectrum... Figure 5 The differences were initially observed, indicating the loading of sunitinib. Furthermore, X-ray photoelectron spectroscopy was used to analyze the characteristic functional groups and molecular skeleton of Sun@M-Lut: the CO bond signal at approximately 286.2 eV in the C1s spectrum and the -NH-C characteristic peak at approximately 400.5 eV in the N1s spectrum confirmed the successful formation of the Schiff base bond; the F1s characteristic peak at approximately 686.9 eV corresponded to the CF bond of sunitinib, confirming its successful loading. Figure 6 In addition, Fourier transform infrared spectroscopy (…) Figure 7 The data shows that Sun@M-Lut is between 1650 and 1750 cm. -1 The presence of a C=O characteristic peak at this location confirms successful encapsulation of sunitinib. Simultaneously, the peaks at 3200–3500 cm⁻¹ indicate successful encapsulation. -1 The intensity of the NH stretching vibration, the C=O absorption peak, and the 1500~1600 cm⁻¹ are enhanced. -1 The characteristic absorption of the benzene ring at the site proves that luteolin achieves effective grafting via Schiff base bonds. Furthermore, through... 1 H NMR spectroscopy analysis of the molecular structure of Sun@M-Lut ( Figure 8 The spectrum showed characteristic peaks belonging to sunitinib (146.54 ppm) and luteolin (148.58 ppm), and a characteristic resonance peak representing the carbonyl carbon of Schiff base formation appeared at 181.44 ppm, confirming the successful assembly of the Sun@M-Lut dual-drug delivery system at the molecular level.

[0123] Based on the above molecular characterization results, the drug release behavior of this nanocarrier was investigated under isothermal shaking conditions at 37℃ in phosphate-buffered saline (PBS) at pH 7.4 (physiological environment) and pH 6.0 (acidic microenvironment for osteoarthritis), respectively. The cumulative release of luteolin was quantitatively determined by high-performance liquid chromatography at a detection wavelength of 329 nm. Figure 9 The release process of sunitinib was monitored using ultraviolet-visible absorption spectroscopy. Figure 10 Luteolin is coupled to the carrier backbone via acid-sensitive Schiff base bonds, resulting in a cumulative release of only 26.50% under neutral conditions (pH 7.4), while a significant burst release occurs under acidic conditions (pH 6.0), reaching 58.22%. In contrast, sunitinib exhibits stable and sustained release characteristics throughout the observation period, with release behavior almost unaffected by pH. After approximately 9 days, the release curves of both drugs tend to plateau. In summary, the series of characterization results demonstrate that this study successfully constructed a pH-sensitive Sun@M-Lut nanocarrier with time-controlled drug release capability, which can remodel the pathological microenvironment of inflammation and hypervascularization, thereby promoting meniscal cartilage regeneration.

[0124] Example 5 Due to the high fluidity of synovial fluid within the knee joint cavity, nanoparticles cannot maintain a stable local drug concentration in vivo, making it difficult to achieve sustained in-situ drug release. To overcome these limitations, this method disperses Sun@M-Lut nanoparticles in a CSMA / HANB double-crosslinked hydrogel system to prepare a Sun@M-Lut / HC composite hydrogel. Its mechanism of action is that during UV crosslinking, HANB covalently integrates into the CSMA network via free radical copolymerization; electrostatic interactions and hydrogen bonds also improve the compatibility of the two components. Secondly, under UV irradiation, HANB releases aldehyde groups that form pH-responsive Schiff base bonds with the primary amino groups of adjacent HANB chains. These acid-sensitive Schiff base bonds can responsively break in the acidic microenvironment of inflammation, thereby achieving time-sequential local drug release at the site of meniscus injury. Figure 11 As shown, after irradiation with ultraviolet light (365nm, 20mW / cm²), 2 Afterwards, the hydrogel precursor transforms from a solution state to a gel state. Scanning electron microscopy results ( Figure 12 The results showed that the hydrogel possesses a microporous structure; dot-like structures were visible on the surface of Sun@M-Lut / HC, which are traces of nanocarriers embedded within the hydrogel matrix. Pore structure analysis indicated that the introduction of nanocarriers reduced both the pore size and porosity of the hydrogel. This change can both prolong and stabilize the drug release process and improve the mechanical strength of the hydrogel.

[0125] Furthermore, meniscus replacement materials need to simultaneously consider tensile strength, compressive load-bearing capacity, and ductility to adapt to the complex biomechanical environment of the knee joint. This study evaluated the mechanical properties of hydrogels with different amounts of Sun@M-Lut nanocarriers through cyclic tensile-compression mechanical testing. Figure 13 The Sun@M-Lut20 / HC composite hydrogel achieves an optimal balance between strength and toughness, can withstand moderate stress, exhibits significantly improved tensile strain, and demonstrates excellent cyclic loading stability. Combined with biocompatibility results, Sun@M-Lut20 / HC confirms that it possesses both good biocompatibility and mechanical properties. Therefore, 20 μg / mL of Sun@M-Lut / HC was selected as the optimal formulation for subsequent studies. Tensile and compression tests ( Figure 14 and Figure 15 The results show that the Sun@M-Lut / HC composite hydrogel exhibits a maximum compressive stress of approximately 600 kPa and a maximum tensile strain of approximately 140% at 80% compressive strain, which meets the mechanical requirements of a natural meniscus. Rheological testing ( Figure 16 The results showed that the storage modulus (G′) of Sun@M-Lut / HC was much higher than the loss modulus (G″), indicating that the introduction of nanoparticles improved the elasticity and load-bearing capacity of the hydrogel. In the rheological dynamic amplitude scanning test, the storage modulus G′ was significantly greater than the loss modulus G″, reflecting the material's good structural integrity. Specifically, the storage modulus of Sun@M-Lut / HC was approximately 3000 Pa, significantly higher than that of pure HC hydrogel (approximately 2400 Pa), proving that nanoparticles can enhance the hydrogel network structure and improve its mechanical stability.

[0126] In phosphate-buffered saline (PBS) containing hyaluronidase (100 U / mL), there was no significant difference in the degradation rate between HC hydrogel and Sun@M-Lut / HC hydrogel. Figure 17 After 10 hours of incubation, the mass retention rates of both were 23% ± 4%, indicating that the addition of the nanocarrier did not alter the expected biodegradation behavior of the materials. Simultaneously, both HC and Sun@M-Lut / HC hydrogels exhibited moderate swelling characteristics in PBS, reaching approximately 150% swelling rate after 12 hours and then tending towards equilibrium. Figure 18 Prior to in vivo implantation, this study evaluated the biocompatibility and potential cytotoxicity of the hydrogel system to ensure its safety and efficacy. The hydrogel was co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 1, 3, 7, and 14 days; live and dead cell staining was performed. Figure 19 This study confirmed that the hydrogel had no significant cytotoxicity and could support the efficient proliferation and migration of bone marrow mesenchymal stem cells within the gel matrix. Hemolysis assay ( Figure 20The results showed that the absorbance of the experimental group was significantly lower than that of the positive control group, confirming the good hemolytic compatibility of the material and laying the foundation for subsequent in vivo experiments. Based on the above characterization results, this study successfully constructed a pH-sensitive, time-controlled drug release Sun@M-Lut nanocarrier and integrated it into a mechanically matched, implantable, self-healing, cartilage-targeting CSMA / HANB double crosslinked hydrogel system, thereby establishing a multi-level drug delivery system.

[0127] Example 6 Osteoarthritis can induce persistent inflammation within the joint cavity, further aggravating meniscus damage and hindering the meniscus's self-repair. Therefore, Sun@M-Lut first improves the adverse inflammatory microenvironment in the meniscus region, constructing a stable microecology conducive to cartilage regeneration and meniscus remodeling.

[0128] Good cell compatibility and blood compatibility are indispensable evaluation indicators for drug biomaterials. Cell counting kit-8 (CCK-8) assay ( Figure 21 This study confirmed that Sun@M-Lut exhibits excellent cell compatibility with RAW 264.7 macrophages and bone marrow mesenchymal stem cells (BMSCs). To evaluate the regulatory effect of this material on the inflammatory microenvironment, an inflammatory model was constructed using 100 ng / mL lipopolysaccharide (LPS). Immunofluorescence (IF) staining was used to analyze the inflammatory response. Figure 22 The cells were labeled with CD86, a marker for M1 macrophages, and CD206, a marker for M2 macrophages. In the Sun@M-Lut treatment group, the fluorescence intensity of CD86-positive cells decreased, while the fluorescence intensity of CD206-positive cells increased. Flow cytometry analysis ( Figure 23 Quantitative studies confirmed that Sun@M-Lut treatment significantly reduced the proportion of M1 macrophages while increasing the proportion of M2 macrophages. The anti-inflammatory activity of Sun@M-Lut was further evaluated using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Figure 24 Compared with the LPS group, the expression of pro-inflammatory genes (interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β)) was downregulated in the Sun@M-Lut+LPS group. Furthermore, the expression levels of anti-inflammatory mediators (interleukin-10 (IL-10), transforming growth factor-β (TGF-β), and interleukin-18 (IL-18)) were significantly upregulated in all groups containing luteolin; while the expression of anti-inflammatory factors in the mesoporous silica nanoparticle (MSN) group and the Sun@MSN group remained at low levels. Western blot results (…) Figure 25The results were consistent with those obtained by qRT-PCR, further demonstrating the anti-inflammatory effect of Sun@M-Lut. Secondly, during excessive inflammatory responses, reactive oxygen species (ROS) further exacerbate local tissue damage, leading to persistent chronic inflammation and inhibiting cartilage regeneration. The bisphenol structure of luteolin in Sun@M-Lut endows it with excellent ROS scavenging ability. Therefore, to evaluate the antioxidant capacity of the Sun@M-Lut nanosystem, this study used 0.4 mM hydrogen peroxide (H2O2) to construct a cellular oxidative stress model. Free radical scavenging activity was detected by the 2,2-diphenyl-1-picrylhydrazine (DPPH) method and the 2,2′-azino-bis(3-ethylbenzothiazol-6-sulfonic acid) (ABTS) assay. Figure 26 MSN-Lut and Sun@M-Lut significantly enhanced the scavenging efficiency of DPPH and ABTS free radicals, with more pronounced decolorization effects from oxidizing agents. Simultaneously, the mRNA expression levels of key antioxidant genes such as superoxide dismutase 1 (SOD1), glutathione peroxidase 1 (GPX1), and catalase (CAT) were significantly upregulated. Figure 27 Intracellular reactive oxygen species (ROS) levels were detected at the cellular level using the 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) probe. Figure 28 Compared to the hydrogen peroxide-treated group, the fluorescence intensity of the Sun@M-Lut-treated group was significantly reduced. Figure 29 As shown, this study quantitatively detected superoxide dismutase-like and glutathione peroxidase-like activities. The results indicate that Sun@M-Lut possesses superoxide dismutase-like activity, capable of converting superoxide anions (·O2) into superoxide dismutase-like substances. - The superoxide anion (·O2) is converted into hydrogen peroxide; Sun@M-Lut also possesses glutathione peroxidase-like activity, which can promote the decomposition of hydrogen peroxide into water. - ) and hydroxyl radical (·OH) levels were measured in detail. Figure 30 The results were consistent with the overall trend of reactive oxygen species changes: Sun@M-Lut effectively scavenged dihydroethidium (DHE)-labeled superoxide anions and hydroxyl radicals detected by hydroxyphenylfluorescein (HPF). These results confirm that Sun@M-Lut possesses strong antioxidant activity and can effectively scavenge reactive oxygen species in the inflammatory microenvironment.

[0129] In summary, within the pathological microenvironment of osteoarthritis, Sun@M-Lut nanospheres can induce macrophages to polarize from a pro-inflammatory M1 phenotype to an anti-inflammatory and pro-repair M2 phenotype, upregulating anti-inflammatory cytokines such as transforming growth factor-β (TGF-β) and interleukin-10 (IL-10); simultaneously, they effectively scavenge reactive oxygen species and alleviate oxidative stress. This dual pH-responsive cascade therapy can simultaneously improve both the inflammatory and oxidative microenvironment, preventing cell damage caused by the accumulation of reactive oxygen species and creating a suitable microenvironment for subsequent cartilage repair and regeneration.

[0130] Example 7 Because the peripheral region of the natural meniscus is relatively richly vascularized, while the central region is avascular, effective repair of the meniscus cartilage requires inhibiting excessive pathological angiogenesis. Sun@M-Lut can specifically block the vascular endothelial growth factor A (VEGFA) signaling pathway, thereby preventing pathological changes caused by vascular invasion of the cartilage repair area. Figure 31 As shown, the in vitro lumen formation assay results revealed significant differences in the tube-forming ability of human umbilical vein endothelial cells (HUVECs) cultured on Matrigel. The total lumen length in the Sun@M-Lut group was significantly lower than that in the control group, confirming that Sun has an anti-angiogenic effect. Furthermore, the crystal violet staining results of the Transwell migration assay (…) Figure 32 This indicates that the number of migrating cells in the Sun@M-Lut group ( Figure 33 The cell migration rate was significantly lower than that of the blank control group and the single-drug group, indicating that Sun@M-Lut can effectively inhibit the chemotactic migration of human umbilical vein endothelial cells. The cell migration rate of the control group was approximately 3-4 times that of the Sun@M-Lut treatment group. Real-time quantitative PCR (qRT-PCR) analysis ( Figure 34 The results showed that, compared with the untreated group, the mRNA expression level of the angiogenesis-related gene VEGFA was significantly downregulated in the Sun-treated group; and the downregulation effect was most significant in the Sun@M-Lut group. Western blotting assay (…) Figure 35 Further confirmation that VEGFA expression was continuously reduced in the Sun@M-Lut group indicates that the nanoparticles can inhibit angiogenesis. The expression of chondrogenic markers SOX9 and COL II was upregulated, while COL I expression was decreased. Alsin blue staining ( Figure 36 The results showed increased glycosaminoglycan deposition in the Sun@M-Lut group, manifested as strong blue positive staining, with both staining intensity and distribution range superior to the control group and the single-drug group. These molecular characteristics strongly suggest that the repaired tissue formed a hyaline cartilage phenotype, rather than fibrocartilage or fibrotic repair tissue.

[0131] Example 8 like Figure 37As shown, Sun@M-Lut aims to modulate the pathological microenvironment in vivo and promote cartilage regeneration. Square polycaprolactone (PCL) scaffolds with dimensions of 6×6×2 mm were prepared by 3D printing. The nanoparticles were mixed with HC hydrogel to prepare a formulation containing 3×10... 7 1 cell, 20 μg / mL -1 The cell-carrying hydrogel precursor of Sun@M-Lut was used to obtain a square hydrogel component with a side length of 6 mm. This component was then impregnated and filled into a PCL scaffold. Figure 38 To further clarify the specific role of nanoparticles in chondrogenic differentiation, the components were divided into three experimental groups (HC-PCL, MSNs / HC-PCL, and Sun@M-Lut / HC-PCL) and subcutaneously implanted into nude mice. Figure 39 ).

[0132] After 8 weeks of in vivo culture, no significant differences were observed in the gross morphology of the components removed from each group. Figure 40 To comprehensively assess tissue regeneration ( ). Figure 41 Hematoxylin-eosin (H&E) staining, safranin O (SO) staining, and immunofluorescence staining of α-smooth muscle actin (α-SMA) were performed on tissues retrieved 8 weeks after implantation. Immunohistochemical results further confirmed that the Sun@M-Lut / HC-PCL composite scaffold significantly downregulated vascular endothelial growth factor A (VEGFA) expression while upregulating COL II expression. Furthermore, the Young's modulus of the HC-PCL matrix matches that of the natural meniscus, providing stable mechanical support, and the nanoparticle loading does not compromise the scaffold's mechanical properties. Quantitative gene expression analysis (…) Figure 42 The results showed that the levels of cartilage-specific markers agglutinin (ACAN), sex-determining region Y-box protein 9 (SOX9), and COL II were significantly upregulated in the Sun@M-Lut / HC-PCL group. In conclusion, combining 3D bioprinting with controllable drug delivery is an effective strategy for meniscus regeneration. Sun@M-Lut / HC-PCL can inhibit pathological angiogenesis and promote cartilage matrix deposition through the sustained release of bioactive molecules, while simultaneously providing mechanical support and regulating the immune microenvironment.

[0133] Example 9 To elucidate the molecular mechanism of Sun@M-Lut-mediated meniscus regeneration, this study constructed an in vitro Transwell co-culture system that mimics the acidic and pro-inflammatory microenvironment of early osteoarthritis and performed RNA sequencing (RNA-seq) analysis. Bioinformatics analysis showed that Sun@M-Lut can construct a multi-level regulatory network centered on the TLR2-HIF1α-TGFβ3 axis, simultaneously regulating inflammatory responses, oxidative stress, pathological angiogenesis, and cartilage matrix homeostasis. KEGG pathway analysis ( Figure 43 Multiple core signaling pathways significantly regulated by Sun@M-Lut were identified, covering the Toll-like receptor signaling pathway, the vascular endothelial growth factor (VEGF) signaling pathway, and the extracellular matrix (ECM) assembly pathway.

[0134] Key differentially expressed gene heatmap ( Figure 44 The results showed that Sun@M-Lut treatment significantly downregulated the expression of pro-inflammatory and degenerative genes such as TLR2, HIF-1α, and MMP13. Abnormal TLR2 activation severely disrupts macrophage polarization homeostasis, exacerbating local inflammatory infiltration and tissue damage. Sun@M-Lut downregulation of TLR2 effectively reversed the disordered inflammatory microenvironment and alleviated inflammation-mediated cartilage damage. Conversely, Sun@M-Lut significantly upregulated the expression of key genes involved in chondrocyte proliferation, differentiation, and tissue repair, such as SOX9, BMP6, and TGFβ3. This study used AutoDock software to perform molecular docking of luteolin with sunitinib and its core target protein. Figure 45 This indicates that luteolin can alleviate early meniscal inflammation in osteoarthritis by interfering with TLR2 / TIFA-related inflammatory signal transduction. Sunitinib inhibits VEGFA-mediated pro-angiogenic activity by regulating the FLI1-VEGFA regulatory axis, thereby inhibiting pathological angiogenesis. In summary, molecular docking results structurally confirm that luteolin and sunitinib can regulate inflammatory responses and angiogenesis, respectively. It is clear that Sun@M-Lut, through a multi-level regulatory mechanism of TLR2-HIF1α-TGFβ3, reshapes the pathological microenvironment of osteoarthritis, restores a stable hypovascular microenvironment, and promotes stem cell differentiation into chondrocytes to achieve meniscal cartilage regeneration.

[0135] Example 10 To explore the feasibility of this engineered construct for functional regeneration of the meniscus, this study constructed an osteoarthritis (OA) meniscus injury model in New Zealand white rabbits and systematically evaluated the in vivo therapeutic effect of the Sun@M-Lut nanoplatform and its ability to regulate in situ cartilage regeneration. Figure 46 Meanwhile, a semi-circular polycaprolactone (PCL) scaffold (11 mm long, 8 mm wide, and 2 mm high) replicating the anatomical contour of the natural medial meniscus was fabricated using 3D bioprinting to provide structural and mechanical support. This study introduced an arginine-glycine-aspartic acid (RGD) functionalized peptide with excellent cell recognition and adhesion-promoting properties to enhance cell adhesion and optimize the integration of the cell-scaffold complex. Subsequently, bone marrow mesenchymal stem cells (BMSCs), the RGD functionalized peptide, and the Sun@M-Lut / HC composite hydrogel (Sun@M-Lut: 20 μg / mL) were incorporated. -1 Cell density: 6×10 7 mL-1 ) are encapsulated inside the support frame ( Figure 47 );according to Figure 48 The surgical procedure shown involves implanting the obtained bioactive construct into the meniscus resection site. Magnetic resonance imaging results showed that in the Sun@M-Lut / HC-PCL treatment group, meniscus signal intensity was restored, articular cartilage thickness was preserved, and there was no significant joint effusion or subchondral bone marrow edema, a stark contrast to the untreated osteoarthritis model group. Figure 49 The transplanted sample was retrieved 12 weeks post-implantation for systematic morphological and histological evaluation. Footprint analysis ( Figure 50 The results showed that, compared to the osteoarthritis model group, the gait function of the animals treated with Sun@M-Lut / HC-PCL was almost completely restored. Ink imprint uniformity, stride length (…) Figure 51 All patients recovered to levels similar to the control group, and the affected limbs of the subjects did not exhibit significant pain avoidance behaviors, compensatory gait changes, or decreased weight-bearing capacity. These results indicate that the Sun@M-Lut / HC-PCL stent can effectively relieve pain caused by osteoarthritis, improve limb weight-bearing and motor function, and its therapeutic effect is significantly superior to that of the MSNs / HC-PCL stent.

[0136] Gross observation shows that the regenerated medial meniscus in the Sun@M-Lut / HC-PCL group replicates the gross anatomical structure of the natural meniscus tissue, with smooth articular surfaces, a clear semi-circular outline, and seamless integration with surrounding host tissue. Figure 52 To further evaluate the in vivo tissue repair effect of the scaffold, hematoxylin-eosin (H&E) staining and safranin O (SO) staining were performed on the samples. Figure 53 The histological results of the Sun@M-Lut / HC-PCL group showed significant improvement: collagen fibers were densely and regularly arranged, and the degree of inflammatory cell infiltration was mild; a large amount of glycosaminoglycan deposition was observed in the repaired tissue, and cartilage matrix synthesis was vigorous. More histological analysis results ( Figure 54 The results showed that the Sun@M-Lut / HC-PCL group exhibited a regionalized distribution pattern of meniscus cell phenotype and extracellular matrix (ECM) deposition, consistent with the heterogeneous collagen structure characteristics of the natural meniscus. Immunofluorescence quantitative analysis of vascular endothelial growth factor A (VEGFA) and tumor necrosis factor-α (TNF-α) indicated that the expression levels of these two factors in the Sun@M-Lut / HC-PCL group were significantly lower than those in the MSNs / HC-PCL group. Further evaluation of cartilage regeneration potential using the scoring criteria established by the International Cartilage Repair Society confirmed that the Sun@M-Lut / HC-PCL group could achieve good cartilage regeneration. Figure 55In summary, the above results demonstrate that the Sun@M-Lut / HC-PCL system is a highly promising translational research strategy that can be used for the functional repair of articular cartilage defects and complex meniscus injuries associated with osteoarthritis.

[0137] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A dual-drug nanocomposite particle, characterized in that, Including mesoporous silica nanoparticles, sunitinib, and luteolin; Sunitinib is loaded within the mesoporous channels of the mesoporous silica nanoparticles, and luteolin is attached to the surface of the mesoporous silica nanoparticles. The surface of the mesoporous silica nanoparticles is subjected to amination treatment to form amino groups, and luteolin forms Schiff base bonds with the amino groups.

2. The dual-drug nanocomposite particles according to claim 1, characterized in that, The average particle size of the dual-drug nanocomposite particles is 270±30 nm.

3. A method for preparing dual-drug nanocomposite particles as described in claim 1 or 2, characterized in that, include: Preparation of mesoporous silica nanoparticles; Sunitinib was loaded into the mesoporous channels of the mesoporous silica nanoparticles; Surface amination treatment was performed on mesoporous silica nanoparticles loaded with sunitinib. Luteolin is reacted with surface-aminated mesoporous silica nanoparticles to form Schiff base bonds between luteolin and the amino groups on the surface of the mesoporous silica nanoparticles, thus obtaining the dual-drug nanocomposite particles.

4. The method for preparing dual-drug nanocomposite particles according to claim 3, characterized in that, Sunitinib is loaded into the mesoporous channels of the mesoporous silica nanoparticles by ultrasonic treatment.

5. A hydrogel composite, characterized in that, The hydrogel composite comprises a hydrogel matrix and dual-drug nanocomposite particles as described in claim 1 or 2 dispersed in the hydrogel matrix.

6. The hydrogel composite according to claim 5, characterized in that, The hydrogel matrix also includes bone marrow mesenchymal stem cells.

7. A method for preparing the hydrogel composite as described in claim 5 or 6, characterized in that, The hydrogel composite is obtained by photocrosslinking and curing of o-nitrobenzyl alcohol-modified hyaluronic acid, chondroitin sulfate methacrylate, dual-drug nanocomposite particles as described in claim 1 or 2, and a photoinitiator.

8. The application of the dual-drug nanocomposite particles as described in claim 1 or 2 in the preparation of tissue-engineered menisci.

9. A tissue-engineered meniscus, characterized in that, Includes a meniscus support and the hydrogel composite as described in claim 5 or 6 within the meniscus support.

10. A method for preparing the tissue-engineered meniscus of claim 9, characterized in that, include: The dual-drug nanocomposite particles as described in claim 1 or 2 are added to a hydrogel system formed by o-nitrobenzyl alcohol-modified hyaluronic acid and chondroitin sulfate methacrylate. Bone marrow mesenchymal stem cells were added to the hydrogel system and mixed. Polycaprolactone meniscus scaffolds were fabricated using bio-3D printing technology. The hydrogel mixture containing the dual-drug nanocomposite particles and bone marrow mesenchymal stem cells was cast into the polycaprolactone meniscus scaffold and photocrosslinked to obtain the tissue-engineered meniscus.

Citation Information

Patent Citations

  • Cartilage regeneration using injectable in situ polymerizable collagen compositions containing chondrocytes or stem cells

    CN117915933A

  • Composition for repairing meniscus, nano-particles, hydrogel material and preparation method and application thereof

    CN121754724A

  • Microenvironment-imitated composite scaffold and application thereof in anisotropic regeneration of meniscus cartilage

    CN122005941A

  • Novel quaternary ammonium salt grafted mesoporous silicon reinforced antibacterial dental composite resin and preparation method thereof

    CN122251238A

  • CH-coated SHP099-NPs composite hydrogel as well as preparation method and application thereof

    CN122272631A